Enamel multidien biological timing and body size variability among individuals of Chinese Han and Tibetan origins - Hakan Karaaslan; Jeffrey Seckinger; Amel Almabrok; Bin Hu; Hui Dong; Dengsheng Xia; Tsering Dekyi; Russell T. Hogg; Jian Zhou; Timothy G. Bromage (Taylor & Francis Group, 2021)
Aims To measure the number of days of enamel formation between periodic striae of Retzius growth lines, the Retzius periodicity (RP), and to compare this multi-day, or multidien rhythm, to body height and weight among people from Beijing, China and Lhasa, Tibet/China. Subjects and methods Subjects requiring dental extractions from clinics in Beijing, China (N = 338) and Lhasa, Tibet/China (N = 227) provided a tooth and body size information. Multiple observers examined histological sections of the teeth and recorded RP. RP values were statistically compared to body height and weight. Results In Beijing and Lhasa samples, respectively, average height was 166.38 and 165.70 cm, average weight was 59.53 and 66.53 kg, and average RP was 7.47 and 7.69 d. Statistically significant differences were found between Beijing and Lhasa weight and RP means. Correlations for height and weight against RP were significant, but only comparatively strong for height. Conclusions Supporting the negative correlation presented in previous studies, RP is negatively associated with height and weight among a large intraspecific sample of people from Beijing and Lhasa. RP represents a metabolic-mediated multidien biological timing mechanism responsible for the rate of cell proliferation and maintenance of the body.